Narrative features of the play “Stolen Happiness” by I. Franko (literary and stage versions) - Проценко, Катерина Володимирівна (The Journal of V. N. Karazin Kharkiv National University. Series “Philology”, 2019)
In this article is observed the narrative features of the play “Stolen Happines” by Ivan Franko and its stage version by producer Lilia Petrenko. The research is carried out with the help of narrative and comparative analysis. The urgency of the work is confirmed by the fact that no one succeeded in comparing the text of the "Stolen Happiness" of the nineteenth and twenty centuries. Such a conclusion is made on the basis of the analyzed works of literary critics and art critics. The author of the article uses such key terms of naratology as event, plot, time and space. These concepts help to understand the features of texts and allow you to compare the drama and its modern stage version. In each of the five acts of Ivan Franko’s drama, the micro, mini- and actual event are determined. The scene version contains two actions which are also considered under this scheme. Time and space were also considered in detail in the example of two texts. The author used G. Zhenet’s theory of narrative movements. The researcher came to the conclusion that Ivan Franko and Lilia Petrenko, by virtue of their capabilities, achieved the desired result. Using various types of art, the authors have created original works that interest the readers and the viewers for more than two centuries. Ivan Franko and Lilia Petrenko is focused on micro and mini events in different ways, however, they come to the main event of "Stolen Happiness" – the assassination of Mikhail Gurman. Time also unfolds in the texts in different ways. In the drama it is stretched, and in the stage reception, on the contrary, is narrowed. Lilia Petrenko resorted to receiving the alignment of time and spatial markers in her play. It makes this play eternal.